LEARNING ORGANIZATION ON THE IMPLEMENTATION OF E- GOVERNMENT IN THE CITY OF MAKASSAR - Sadiq, A. Ali Imran; Haning, Mohammad Tahir; Nara, Nurdin; Rusdi, Muhammad (The journal of contemporary issues in business and government, 2021)
This study of learning organization on the implementation of e-government in the city of Makassar, the Transition of “information society”, putting the human element and the knowledge in the organization as one of the fundamental elements and even put the role of knowledge or intellectual capital in the organization as an important element which requires the expansion of the set of skills that are “hard” (technology) and “soft” (interpersonal and communication) in a balanced way. E- government has become a priority program of government agencies, both at the center and regions all over the world, who not only viewed as a project that became a trend among the government, but it leads to how to improve the accountability, transparency and effectiveness as well as the quality of service that is expected to lead to the creation of good government. The study site is located in the city of makassar. The method used in this research is included in the descriptive qualitative research, the results of his research are the Makassar City Government implement a mechanism of Learning Organization in the form of the creation of top management support, implementation of training and development of human resources based on the competence, the development of feedback on all fronts as well as the provision and development of mis (Management Information System) within the framework of e-government. The application of the mechanism of the learning Organization happens automatically as a result of the policies of the central government in implementing e-government.